Angelagrion gen. nov. with description of A. nathaliae sp. nov. and A. fredericoi sp. nov. from Brazil (Odonata: Coenagrionidae) - Lencioni, Frederico A. A. (Zootaxa, 2008)
A new genus of Coenagrionidae is described from Brazil, Angelagrion (type species Angelagrion fredericoi sp. nov.) including two new species, A. fredericoi sp. nov. and A. nathaliae sp. nov.. The new genus is characterized by an enormous and modified internal fold of genital ligula, abdominal segments S8-10 dark brown or black contrasting with mostly bluish abdomen, sternum of S8 in males with a circular bluish-white spot, and short CuA.